Design a Photobioreactor for Microalgae Cultivation with the IOTs (Internet of Things) System - Ayi Rahmat; Indra Jaya; Totok Hestirianoto; Dedi Jusadi; Mujizat Kawaroe (Journal Omni-Akuatika, 2020)
Internet of Things (IOTs) is an evolution of the concept of internet use that aims to expand the benefits of internet connectivity that is connected continuously with the ability to control remotely (remote control), share data (data sharing), carry out continuous monitoring (real time monitoring) and current (up to date). This research related to the cultivation of microalgae as a source of food and energy of the future, in the design of photobioreactors that are integrated with IoT, so that it can be monitored continuously, controlled and used as a model for the development of greater microalgae cultivation technology. Cultivation in this study was a closed system photobioreactor, will produce microalgae that are not contaminated by external contaminants, growth analysis can be done based on the parameters that influence it, including the cultivation room temperature, lighting level (luminance), and the color of water in the photosynthesis process of microalgae, and also control of water circulation. Visualization of controlled parameters includes, temperature parameters, light intensity, water color changes. The observed parameters will be displayed in a graphical user interface (GUI) in real time using the internet. The advantages of this system can see the growth of microalgae in detail over time, and obtained raw data that can be processed for various research purposes.